Evolution study of some physical and motor parameters during the different periods of sport season of the footballers U20, playing in Constantine’s professional league teams - Gasmi, Abdelmalek; Benyamina, Mohamed Mehdi (Journal of Human Sciences, 2020)
Objective: Our research consists of analyzing the evolution of some physical and motor   parameters during the different periods of the sports season of the footballers U20, playing in Constantine’s professional league teams.Methodology: Our approach was based on carrying out physical tests measuring some physical and motor qualities deemed to be decisive for achieving performance in football, and all this to compare the evolution of these parameters during a sports season.Sample: 52 players (U20) playing in the professional league (CSC - ASK) during the 2015/2016 season, took part in this study. The subjects agreed to perform different tests during the three checkpoints (C1-C2-C3), namely, speed tests on 10-20-30M, the long jump test, the five jump test, Barrow test, and 20 meters Luc-Léger shuttle test.Conclusion: The research results revealed significant differences in all physical and motor parameters studied of footballers (U20); these parameters have evolved during the different periods of the season with more than significant differences for the difference pair (C1-C3) which suggests that modifications and changes are acquired more quickly than others during all sports season.